License plate recognition - Chowdhury, Mohammed Abrar Ahasan; Rozaik, Soyelim Al; Shanto, Mahedi Hasan (Brac University, 2023)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science, 2023.